Examining Relation Formation Across Consistent and Conflicting Texts. Issue 2 (7th February 2021) - List, Alexandra; Du, Hongcui; Lee, Hye Yeon
ABSTRACT: When using the Internet to learn about complex topics or issues, students often encounter information that is both complementary and conflicting. Building on prior work identifying differences in how students reason about multiple conflicting texts, we examine students' connection formation and summative conceptualization of texts systematically designed to vary in a number of ways. We examine students' connection formation and summative conceptualization of texts introducing consistent or conflicting main ideas, accompanied by supporting reasons that are overlapping or distinct. We investigate the extent to which students form three types of connections across texts: evidentiary (i.e., corroborating specific information across texts), thematic (i.e., connecting main ideas), and contextual (i.e., comparing texts' meta-features such as author). Moreover, we analyze how students summatively describe texts related to one another in a variety of ways. In general, the text condition reflecting the greatest degree of cross-textual consistency (i.e., texts that included consistent main ideas and that presented overlapping supporting reasons) resulted in students being able to form a greater number of cross-textual connections, overall, and more evidentiary and thematic connections, in particular, as compared to the most discrepant text condition (i.e., when texts had conflicting main ideas and presented distinct supporting reasons). Discrepant main ideas across texts were found to increase students' contextual connection formation.